An Ethnographic Study of Barriers to Cancer Pain Management and Opioid Availability in India. (22nd April 2014) - LeBaron, Virginia; Beck, Susan L.; Maurer, Martha; Black, Fraser; Palat, Gayatri
Abstract: Background: The world's global cancer burden disproportionally affects lower income countries, where 80% of patients present with late-stage disease and have limited access to palliative care and effective pain-relieving medications, such as morphine. Consequently, millions die each year with unrelieved pain. Objective: The objective of this study was to examine barriers to opioid availability and cancer pain management in India, with an emphasis on the experiences of nurses, who are often the front-line providers of palliative care. Methods: Fifty-nine participants were recruited using a purposive, snowball sampling strategy. Ethnographic data collection included in-depth, semistructured interviews ( n = 54), 400+ hours of participant observation, and review of documents over 9 months at a government cancer hospital in South India. Systematic qualitative analysis led to identification of key barriers that are exemplified by representative quotes. Results: Morphine is more available at this study site than in most of India, but access is limited to patients seen by the palliative care service, and significant gaps in supply still occur. Systems to measure and improve pain outcomes are largely absent. Key barriers related to pain management include the role of nursing, opioid misperceptions, bureaucratic hurdles, and sociocultural/infrastructure challenges. Implications: Interventions must streamline process details of morphine procurement, work within the existing sociocultural infrastructure to ensure opioids reach patients most in need, target unexpected audiences for symptom management education, and account for role expectations of health care providers. Conclusion: Macro- and micro-level policy and practice changes are needed to improve opioid availability and cancer pain management in India. Abstract : We examined barriers to opioid availability and cancer pain management in India, with an emphasis on the experiences of nurses, who are often the front-line providers of palliative care. Interventions must streamline process details of morphine procurement, work within the existing sociocultural infrastructure to ensure opioids reach patients most in need, target unexpected audiences for symptom management education, and account for role expectations of health care providers.